Private transfers to young adult households in the United States and France - Rachel Karen (Luxembourg Income Study (LIS), 2023)
As the transition to adulthood becomes longer and more precarious, there is increasing interest in whether and how families help young adult children navigate various transitions into adult roles. Financial transfers to young adults may be one crucial way for families to support their grown children. Yet such transfers could also reinforce existing inequalities if young adults who have the greatest access to these transfers also occupy privileged positions. This paper analyzes Luxembourg Income Study (LIS) data from 2016-2018 to investigate the distribution of financial transfers among young adult households and the impact of these financial transfers on young adult households' financial well-being in the United States and France. This paper employs a Bourdieusian framework to understand observed differences in the frequency and amount of money transferred to American and French young adult households, as private transfers frequently benefit young adult households with higher levels of social and cultural capital. Findings also suggest that private cash transfers are an important source of financial support for young adults in both countries, particularly for young adults already at lower risks for experiencing poverty. Results from this paper demonstrate one important avenue through which inequality could be reproduced in young adulthood.
Keywords: 330